English Nonverbal Expressions in Communication - Eshmirzayeva Nozima Bahodir qizi (Genius Publishing Group, 2023)
Humans send messages not only with the help of of words, but they can also convey meaning through the usage of facial expressions, eye contact, body language, hand gestures and tone of voice all of which we know as nonverbal communication
Keywords: gestures; contact; language; tone